Resonance Raman kinetic spectroscopy of bacteriorhodopsin on the microsecond time scale. - Campion, A (1977)
Using a rotating disk with a slit of variable width, a continuous wave argon ion laser, and an Optical Multichannel Analyzer for detection, a new technique is reported which should, in principle, be capable of recording resonance Raman spectra with time resolution of 100 ns. The resonance Raman spectra of the intermediates of the photosynthetic cycle of bacteriorhodopsin are recorded on the microsecond time scale. Both the kinetic results and the resonance enhancement profile suggest that deprotonation results in an intermediate preceding bM412 that has an optical absorption maximum at a wavelength longer than that of bM412.